Cross-border mergers and domestic-firm wages: Integrating “spillover effects” and “bargaining effects” - Clougherty, Joseph A; Gugler, Klaus; Sørgard, Lars; Szücs, Florian W (Journal of International Business Studies, 2014)
Two literatures exist concerning cross-border merger activity’s impact on domestic wages: one focusing on positive spillover effects; the other focusing on negative bargaining effects. Motivated by scarce theoretical scholarship spanning these literatures, we nest both mechanisms in a single conceptual framework. Considering the separate phenomena of inward and outward cross-border merger activity, our theoretical model generates three formal propositions: cross-border mergers can lead to wage increases via positive spillover effects; and negative bargaining effects are relatively more dominant when union market power is high, and when merging firms exhibit relatedness. Employing US firm-level panel data on wages combined with industry-level data on unionization and merger activity (covering 1989–2001), we find support for our propositions as inward and outward cross-border merger activity generate positive spillovers to wages, but are more likely to generate firm-level wage decreases when unionization rates are high and when cross-border merger activity is characterized as horizontal. Accordingly, future research on how cross-border mergers affect domestic wages should be mindful that both spillover and bargaining effects are at play, and that the degree of union market power and the relatedness of cross-border merger activity are critical in determining which effect dominates.